MicroRNA Expression Detection Methods - Wang, Zhiguo; Yang, Baofeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book provides comprehensive descriptions of the innovative strategies and methodologies for detecting miRNA expression, their application in miRNA research and their potential as tools for clinical diagnosis and prognosis. It begins with the introduction of the overall concept and strategies of miRNA expression detection methods emphasizing the need of a wide variety of these methods to suit specific requirements for research and clinical examination in laboratories. In the following, each single chapter focuses on an independent, unique method of miRNA detection and is divided into five subsections: summary, introduction, protocol (including materials, instrument, reagent, and procedure), application and limitation, and reference. The development of the technique, the ideas behind it and the mechanisms underlying the method are given in the introduction of each chapter. The step-by-step protocols are detailed in the protocol section. Then, the applications and limitations of the methods are discussed. Finally, the literature citations are listed in reference section. Schematic diagrams are included where needed and appropriate for better illustrating the principle of the methodologies. In addition, flowcharts are also provided to outline the protocols for each of the miRNA expression detection methods. This book is aimed to target both researchers involved in miRNA research of any fields in universities and research institutions and medical practitioners who are interested in developing or utilizing miRNA profiling as a complementary and an alternative strategy for clinical diagnosis of human disease.
General Remarks -- Detection, Profiling, and Quantification of miRNA Expression -- miRNA Microarray Methods -- Microarray and Its Variants for miRNA Profiling -- Northern Blotting Methods -- Northern Blotting and Its Variants for Detecting Expression and Analyzing Tissue Distribution of miRNAs -- In Situ Hybridization Methods -- In Situ Hybridization and Its Variants for Detecting Expression and Analyzing Cellular Distribution of miRNAs -- Real-Time RT-PCR Methods -- End-Point Stem-Loop Real-Time RT-PCR for miRNA Quantification -- miR-Q RT-PCR for miRNA Quantification -- Poly(A)-Tailed Universal Reverse Transcription -- Multiplexing RT-PCR for High-Throughput miRNA Profiling -- miRNA Amplification Profiling (mRAP) -- Cloning Methods -- miRNA Serial Analysis of Gene Expression (miRAGE or SAGE) -- Nanoparticle Methods -- Electrocatalytic Nanoparticle Tags Technique for High-Sensitivity miRNA Expression Analysis -- Nanoparticle-Amplified SPR Imaging for High-Sensitivity miRNA Profiling -- Conducting Polymer Nanowires Technique for High-Sensitivity miRNA Expression Analysis -- Gold Nanoparticle Probe Method for miRNA Quantification -- Other Methods -- Splinted Ligation Method -- Padlock-Probes and Rolling-Circle Amplification -- Invader Assay -- Single Molecule Method -- Enzymatic Method -- Surface-Enhanced Raman Spectroscopy Method -- RAKE Assay -- Bead-Based Flow Cytometric miRNA Expression Profiling -- Bioluminescence miRNA Detection Method -- Molecular Beacon Method -- Ribozyme Method -- Electrocatalytic Moiety Labeling Technique for High-Sensitivity miRNA Expression Analysis -- Circulating miRNA Detection Methods -- Serum and Plasma miRNA Detection -- miRNA Detection from Peripheral Blood Microvesicles -- Detection of Placental miRNAs in Maternal Plasma -- Single-cell miRNA Detection Methods -- Quantitative LNA-ELF-FISH Method for miRNA Detection in Single Mammalian Cell -- Single Cell Stem-Looped Real-Time PCR -- miRNA Function-Reporter Expression Assay -- Whole Mount In Situ Analysis -- Whole Mount In Situ Hybridization (WM-ISH) for miRNA Expression Profiling During Vertebrate Development.
Keywords: Cell biology; Biochemistry; Gene expression; Pharmacology; Gene therapy; Cell Biology; Biochemistry, general; Gene Expression; Pharmacology/Toxicology.; Gene Therapy